2017
DOI: 10.1111/acps.12820
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of lithium after a diagnosis of chronic kidney disease

Abstract: After an initial diagnosis of CKD, patients who are selected by their physicians to continue lithium treatment may not necessarily have an increased risk of developing end-stage CKD. Shifting to an anticonvulsant per se may not be associated with an advantage; however, this requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Furthermore, inclusion of both lithium treatment-naive (i. e., never exposed to lithium) patients and patients who have been treated with lithium previously could be of importance in the interpreta-tion of study results since previous tolerance or intolerance to a study drug may influence the subsequent study group allocation and thereby outcomes of the study [25]. Moreover, in some clinical samples, patients are followed for a brief period of time or data collection is cross-sectional by design [15,16], in contrast to other studies, primarily register-based, where patients are followed longterm or even lifelong, allowing for follow-up on development of renal impairment in patients exposed never, only previously, or still/ continuously [17][18][19][20]26]. Another advantage of register-based based studies is that all cases can more easily be identified (regardless of severity, course of illness, comorbidity, etc.)…”
Section: Study Design Issuesmentioning
confidence: 99%
“…Furthermore, inclusion of both lithium treatment-naive (i. e., never exposed to lithium) patients and patients who have been treated with lithium previously could be of importance in the interpreta-tion of study results since previous tolerance or intolerance to a study drug may influence the subsequent study group allocation and thereby outcomes of the study [25]. Moreover, in some clinical samples, patients are followed for a brief period of time or data collection is cross-sectional by design [15,16], in contrast to other studies, primarily register-based, where patients are followed longterm or even lifelong, allowing for follow-up on development of renal impairment in patients exposed never, only previously, or still/ continuously [17][18][19][20]26]. Another advantage of register-based based studies is that all cases can more easily be identified (regardless of severity, course of illness, comorbidity, etc.)…”
Section: Study Design Issuesmentioning
confidence: 99%
“…Interestingly, a large population‐based study suggested that maintenance treatment with lithium or anticonvulsants is associated with an increased rate of CKD while not necessarily increasing the rate of ESRD 4 . In a follow‐up study, Kessing et al showed that continued lithium treatment after an initial diagnosis of CKD may not necessarily increase the risk of developing ESRD 5 . However, the literature still remains controversial, hindering clinical evidence‐based decisions regarding the optimal time for clinicians to continue or discontinue lithium after a diagnosis of worsening CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, reinitiating lithium treatment in our patient was successful in stabilizing her mood symptoms, ultimately reestablishing her illness remission. Furthermore, the clinical decision was supported by the evidence from Kessing and colleagues 5 who showed that continued lithium treatment after an initial diagnosis of CKD may not necessarily increase the risk of developing ESRD.
Lithium can be used safely in patients with BD and CKD with careful monitoring of renal function. Risks/benefits of lithium treatment should always be weighed against the risk of illness decompensation. Restarting lithium treatment was possible without further decline in renal function. This case highlights the importance of patient‐education and team‐based individualized approach.
…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that patients who continue lithium treatment after a diagnosis of CKD may not necessarily have an increased risk of developing end‐stage CKD. Shifting to an anticonvulsant per se may not be associated with an advantage …”
Section: Discussionmentioning
confidence: 99%